Grafting of 4-pyrrolyphenyldiazonium in situ generated on NiTi, an adhesion promoter for pyrrole electropolymerisation?. (1st September 2016) - Jacques, A.; Chehimi, M.M.; Poleunis, C.; Delcorte, A.; Delhalle, J.; Mekhalif, Z.
Abstract: The present work investigates the grafting of in situ generated 4-pyrrolyphenyldiazonium (Py-PD) on NiTi by two different ways. The first way is the electrografting of Py-PD while the second one is the grafting without electrochemistry at room temperature (spontaneous grafting) or under heating (either conventional heating or induction heating). Both modification routes led to the successful grafting of Py-PD. The hypothesis of a cationic intermediate is proposed for the grafting without electrochemistry since it is thermally activated and the oxidized surface of NiTi is not a reductant. For both modification approaches, the TiO2 surface layer of NiTi has been preserved and the NiTi corrosion resistance improved, an important parameter to preserve/improve the NiTi biocompatibility. The second part of the work is dedicated to the electropolymerization of pyrrole on modified surfaces with the Py-PD as adhesion promoter.